Demyelinating Syndromes in Systemic Lupus Erythematosus: Data From the “Attikon” Lupus Cohort - Nikolopoulos, Dionysis; Kitsos, Dimitrios; Papathanasiou, Matilda; Kapsala, Noemin; Garantziotis, Panagiotis; Pieta, Antigone; Gioti, Ourania; Grivas, Alexandros; Voumvourakis, Konstantinos; Boumpas, Dimitrios; Fanouriakis, Antonis (Frontiers in Neurology, 2022)
Background: Central nervous system (CNS) demyelinating syndromes that occur in the context of systemic lupus erythematosus (SLE) may represent a manifestation of neuropsychiatric lupus (NPSLE), or an overlap of SLE and multiple sclerosis (MS). The differential diagnosis between the two entities has important clinical implications, because the therapeutic management differs. Objectives: To characterize CNS demyelinating syndromes in a large SLE cohort as neuropsychiatric SLE (NPSLE) or SLE-MS overlap, using a multidisciplinary approach and existing diagnostic (for MS) and classification criteria (for SLE) Methods: Patients from the “Attikon” lupus cohort (n=707) were evaluated for demyelinating syndromes. Clinical, laboratory and neuroimaging data were recorded for each patient. Following multidisciplinary evaluation and application of criteria, the demyelinating syndrome was attributed to either SLE or MS. Patients with transverse myelitis were not included in this study. Results: We identified 26 patients with demyelinating syndromes (3.7%). Of them, 12 were diagnosed as primary SLE-demyelination (46.2%) and 14 as overlap SLE-MS (53.8%). The two groups did not differ with respect to rheumatologic and neurologic manifestations, or autoantibodies. SLE patients with demyelination manifested mild extra-CNS disease mainly involving joints and skin, while severe non-CNS manifestations were rare. However, these patients were less likely to have elevated IgG index (OR 0.055 95% CI: 0.008-0.40) and positive oligoclonal bands (OR 0.09 95% CI: 0.014-0.56), as well as brain lesions in the spinal cord, infratentorial, periventricular and juxtacortical regions. A single brain region was affected in 9 SLE-demyelination patients (75%), while all MS-SLE patients had multiple affected brain regions. MS-SLE overlap was associated with increased likelihood of neurologic relapses (OR 18.2, 95% CI: 1.76-188), while SLE-demyelination patients were less likely to exhibit neurological deficits (EDSS>0) at last follow-up visit (50% vs. 78.6% in SLE-MS, respectively). Conclusions: Demyelination in the context of SLE follows a more benign course compared to a frank SLE-MS overlap. Extension of follow-up will ascertain whether SLE-demyelination patients evolve to MS, or this is a bona fide NPSLE syndrome.